The Effect of Target-Throwing Training on the Improvement of Javelin Throw Accuracy among Students at SDN Muncul 01 Setu, South Tangerang City - Gatot Sukartono; Kevin Ramadhan; Bambang Suwito Kusumo; Fikra Azahra; M Hafid Qolbi; Ade Chandra (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aimed to analyze the effect of target-throwing training on improving javelin throw accuracy among elementary school students at SDN Muncul 01 Setu, South Tangerang City. The background of this study was the low level of students’ throwing accuracy, which was influenced by limited variations in training methods and inadequate supporting facilities. A quasi-experimental method with a pretest–posttest control group design was employed, involving 40 students who were divided into an experimental group and a control group. The experimental group received target-throwing training for eight sessions, while the control group participated in conventional javelin throwing instruction. The research instrument was a javelin throw accuracy test administered before and after the intervention. Descriptive analysis showed a significant improvement in the experimental group, with the mean score increasing from 29.90 to 43.40. In contrast, the control group showed a smaller improvement, from 30.30 to 35.10. Statistical analysis using paired sample t-tests and independent sample t-tests indicated that target-throwing training had a significant effect on improving javelin throw accuracy (p < 0.05). These findings confirm that target-throwing training is an effective, safe, and relevant method for physical education instruction to enhance throwing accuracy among elementary school students.